Comprehensive RNA Sequencing in Adenoma-Cancer Transition Identified Predictive Biomarkers and Therapeutic Targets of Human CRC - Mingzhe Zhu; Yanqi Dang; Zhenhua Yang; Yang Liu; Li Zhang; Yangxian Xu; Wenjun Zhou; Guang Ji (Elsevier, 2020)
Specific molecular biomarkers for predicting the transition from colorectal adenoma to cancer have been identified, however, circular RNA (circRNA)-related signatures remain to be clarified. We carried out high-throughput RNA sequencing to determine the expression profiles of circRNAs, microRNAs (miRNAs), and mRNAs in human colorectal cancer (CRC), adenoma, and adjacent normal tissues. We identified 84 circRNAs, 41 miRNAs, and 398 mRNAs that were commonly differentially expressed in CRC and adenoma tissues compared with normal tissues. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and protein-protein interaction (PPI) analyses identified numerous cancer-related hub genes that might serve as potential therapeutic targets in CRC. Competing endogenous RNA (ceRNA) networks, including three circRNAs, three miRNAs, and 28 mRNAs were constructed, suggesting their potential role in cancer progression. Representative differentially expressed RNAs were validated by the Cancer Genome Atlas (TCGA) database and real-time PCR experiments. Receiver operating characteristic (ROC) curve analysis identified three circRNAs (hsa_circ_0049487, hsa_circ_0066875, and hsa_circ_0007444) as possible novel biomarkers predicting the transition from colonic adenoma to cancer. Overall, our findings may provide novel perspectives to clarify the mechanisms of the transition from premalignant adenoma to cancer and identify specific circRNA-related signatures with possible applications for the early diagnosis of and as potential therapeutic targets in CRC.